Pengaruh Tenaga Kerja, Jam Kerja dan Tingkat Harga terhadap Tingkat Produksi Industri Batu Bata di Desa Pulau Pinang Kecamatan Binuang Kabupaten Tapin - Rasidi, Adam; Muzdalifah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research aims to determine the influence of labor, working hours, and price levels on the brick industry production in Pulau Pinang Village, Binuang Sub-district, Tapin District, and the most dominant factor of the three elements. This research uses data analysis tools in software Eviews 9, with multiple linearregression models using the least-squares estimation method. The data used areprimary and secondary. The research results show that labor, working hours, andprice levels significantly affect the level of production both simultaneously andpartially. The factor that offers the most dominant influence in influencing the brickindustry's level of production is the labor factor.